Implementasi Model Pendidikan Gerak Dalam Pembelajaran Aktivitas Ritmik Pola Langkah Pada Siswa Kelas 5 Sekolah Dasar - Yulfita, Nenda; Mahendra, Agus; Nahduddin, Dodo (TEGAR: Journal of Teaching Physical Education in Elementary School, 2018)
This research is driven by the question whether the learning of rhythmic activity on step patterns could be implemented by using movement education or not. This is because the subject of step pattern learning has never or almost never been carried out at all in the school, especially at SDN Pada Asih, Bandung. Therefore, researchers are interested in conducting a study by using Classroom Action Research (CAR) methods, by employing movement education model in the subject. The participants in this study were fifth grade students of Padaasih, totaling 43 students, consisting of 21 male students and 22 female students. The data is collected by means of an observational sheet and analyzed by procentage tendencies. The results of the research in terms of understanding and students ability in performing the steps are as follows: in the first cycle of action I, the average percentage was (37.86%). In cycle I action II, the percentage was (49.58%). In cycle II action I, the  average percentage has increased to (63.53%), and in the cycle II action II, the average percentage was (80.56%). It can be concluded  that the movement education model can be implemented in the learning of the step pattern to the students of grade 5. AbstrakPenelitian ini dilatar belakangi oleh pertanyaan apakah pembelajaran aktivitas ritmik pola langkah dapat diterapkan melalui model pendidikan gerak pada siswa kelas 5 SDN Padaasih. Hal ini didasari kenyataan bahwa pembelajaran aktivitas ritmik pola langkah masih amat jarang dilakukan, untuk tidak mengatakan tidak pernah sama sekali. Dalam penelitian ini, peneliti menggunakan metode Penelitian Tindakan Kelas (PTK). Pengumpulan data dilakukan dengan menggunakan lembar observasi dan analisisnya digunakan teknik persentase. Partisipan dalam penelitian ini adalah siswa kelas 5 SDN Padaasih tahun ajaran 2018/2019 yang berjumlah 43 siswa, terdiri dari 21 siswa putera dan 22 siswa putri. Hasil penelitian pada siklus I tindakan I menunjukkan pemahaman siswa dalam pembelajaran aktivitas ritmik pola langkah mencapai rata-rata persentase (37,86%). Pada siklus I tindakan II mengalami peningkatan rata-rata persentase menjadi (49,58%) Pada siklus II tindakan I menunjukkan peningkatan rata-rata persentase yaitu (63,53%). Pada siklus II tindakan II menunjukkan peningkatan rata-rata persentase yaitu (80,56%). Penelitian ini menyimpulkan bahwa model pendidikan gerak dapat diimplementasikan pada pembelajaran aktivitas ritmik pola langkah pada siswa kelas 5 SDN Padaasih Tahun Ajaran 2018/2019.